2004
DOI: 10.1111/j.0022-202x.2004.23220.x
|View full text |Cite
|
Sign up to set email alerts
|

SPINK5 and Netherton Syndrome: Novel Mutations, Demonstration of Missing LEKTI, and Differential Expression of Transglutaminases

Abstract: Netherton syndrome (NTS) is an autosomal recessive congenital ichthyosis featuring chronic inflammation of the skin, hair anomalies, epidermal hyperplasia with an impaired epidermal barrier function, failure to thrive and atopic manifestations. The disease is caused by mutations in the SPINK5 gene encoding the serine proteinase inhibitor lympho-epithelial Kazal-type inhibitor (LEKTI). Sequence analyses of SPINK5 in seven NTS patients from five different families allowed us to identify two known and three novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 28 publications
(35 reference statements)
10
96
0
2
Order By: Relevance
“…SLPI and SKALP are thus potential physiological inhibitors of ELA2 in the skin, which is in agreement with their specific capacity to inhibit members of the elastase family (31,32). High expression of SKALP has been reported in NS patient skin in response to skin inflammation and recurrent infections (14,33). However, SKALP overexpression is not sufficient to counteract ELA2 hyperactivity, as revealed by in situ zymography on patient skin sections.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…SLPI and SKALP are thus potential physiological inhibitors of ELA2 in the skin, which is in agreement with their specific capacity to inhibit members of the elastase family (31,32). High expression of SKALP has been reported in NS patient skin in response to skin inflammation and recurrent infections (14,33). However, SKALP overexpression is not sufficient to counteract ELA2 hyperactivity, as revealed by in situ zymography on patient skin sections.…”
Section: Discussionsupporting
confidence: 62%
“…We have previ-ously identified serine protease inhibitor kazal-type 5 (SPINK5) as the defective gene in NS (7). The vast majority of causative mutations reported to date lead to the complete absence of the encoded protein, LEKTI (7,(12)(13)(14). LEKTI is expressed in the SG of the epidermis, and we showed that bioactive LEKTI fragments inhibit 3 major proteases involved in SC desquamation, kallikreins (KLK) 5, 7, and 14 (15).…”
Section: Introductionmentioning
confidence: 97%
“…42,43 Immunohistochemical staining confirms FLG deficiency in IV (Figures 1l and m) 44 and reveals absent or reduced expression of lympho-epithelial kazal-type-related inhibitor and SNAP29 in NS and CEDNIK, respectively. [45][46][47] In addition, light microscopy of hair shafts demonstrates 'bamboo hairs' (trichorrhexis invaginata) in NS (Figure 1j) 48 and polarization microscopy of TTD patient hairs reveals a tiger-tail pattern that corresponds to the diagnostic low sulfur protein content (Figure 1i). 49,50 Electron microscopy.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…219,220 Special immunohistochemical procedures can be combined, eg, to confirm filaggrin deficiency in IV, 202,221 or demonstrate absent or reduced expression of LEKTI that supports the diagnosis of NS. [222][223][224] To screen for TGase-1 deficiency in ARCI unfixed cryostat sections are used for the enzyme activity assay. 225,226 Alternatively, superficial SC material can be subjected to a SDS heating test that visualizes absent cross-linked envelopes in TGase-1 deficiency.…”
Section: Use Of Ultrastructural Analysesmentioning
confidence: 99%